Phytochemistry and pharmacological aspects of Tridax procumbens (L.): A systematic and comprehensive review - Varsharani V. Ingole; Pravin C. Mhaske; Sushma R. Katade (Elsevier, 2022)
Background: Tridax procumbens L. (T. procumbens) belongs to the Asteraceae family, is an Ayurvedic herb of Asia with a history of traditional use. T. procumbens have been used from ancient times to treat wounds, skin diseases and to stop blood clotting in folk medicine. It possesses anticoagulant, antileishmanial, antioxidants, anticancer, immunomodulatory agent, insecticidal, anthelmintic cardiovascular, antiseptic, antimicrobial, and insecticidal properties. Purpose: This review article aims to collate past and present updated information on traditional uses, morphology, chemical constituents and pharmacological activities, miscellaneous activities, and relevant patents of this plant, thereby providing useful data for researchers and pharmaceutical, cosmetics-related industries. Methods: A review was collected from various platforms, including Science Direct, Google Scholar, Google patents, PubMed, ACS, Tayler and Francis, Mendeley Desktop databases on traditional uses, morphology, phytochemicals, pharmacological activities, and patents of T. procumbens. The literature search covers original research articles and reviews articles in peer review journals, published up to 2021 using relevant keywords. Chemical structures were drawn using Chem draw ultra 8.0. Total number of 101 references were used in the present review. Results: This review yielded 839 Papers. After the screening method, 101 papers were potentially discussed. Phytochemical investigation revealed more than 138 chemical compounds have been isolated or identified from T. procumbens plant, including 75 isolated and other identified compounds. This plant possesses a variety of chemical compounds including flavonoids, essential oils, saponins, and terpenoids as main secondary metabolites. Diverse pharmacological activities of T. procumbens have a wide range of bioactivities including antimicrobial, antioxidant, anticancer, anti-inflammatory, and wound healing properties. Toxicological knowledge is scarce at this time, and more research is needed on this plant. Conclusions: T. procumbens predominantly shows wound healing, antimicrobial, anti-inflammatory properties traditionally. It is not further supported by the isolation of chemical compounds i.e. lack of bioassay-guided isolation strategies is observed. Several main active chemical compounds are present in the T. procumbens. The pharmacological effects of plant active secondary metabolites of this plant may help to defeat dangerous diseases such as diabetics, cancers, respiratory disorders like the current corona virus COVID -19 upsurge. The present treasury of traditional uses, chemical compounds, and pharmacological activities will be helpful in the future for researchers on T. procumbens in the search for new leads for drug discovery.